Pendengar-Pendengar Radio Di Kulai: Satu Kajian Tentang Ciri-Ciri Dan Tabiat Pendengaran - Devan, Subhadru Kumari (Universiti Sains Malaysia, 1983)
Radio listening habits and characteristics of audiences in Southern Johor , a part of audience research in Malaysia, is the focus of this academic exercise. This descriptive study concentrates on the radio audience of Kulai, in Johor, who are exposed daily to broadcasts from Singapore – a neighbouring country with a different national language.